(untitled) (Revista Internacional de Folkcomunicação, 2024)
This article, produced during the post-doctorate in Argentina, has an essayistic and authorial character in the first person, but when subscribing to Revista Famecos we chose to work together, valuing the partnership and contributions of the internship supervisor. We emphasize the paths not only of systematic research, but a conceptual rhetorical exercise of mediatization, tradition and folkmedia, using authors from the Social Sciences and Communication. Just as a literature review as a research technique, the objectives are the theoretical construction of mediatization and the insertion of tradition, changing its course over time, being impacted by the media and technology; and the appropriation of a communication and media industry in the face of popular demonstrations, as we call the concept of folkmídia. We did not use an empirical object, which requires continuity of investigation in the future. Concluding that in a mediated context between technology, network and multiple languages, aspects of tradition suffer ruptures, gradually mixing a battle between values of permanence and adaptations.